Análisis y cuantificación del magisterio primario en León durante la segunda mitad del siglo XIX - Celada Perandones, Pablo (Estudios humanísticos. Geografía, historia y arte, 1992)
The aim of this article «Analysis and quantifying of Primary teaching in León during the second half of the 19th century» is to analyze the situation of elementary education teachers in León during the aforementioned period, and not only quantifying their number across the different states (Tables), but also attending to other questions such as their training, payments, qualification, school infraestructure, pupils, etc.; such a treatment will help to approach a more objetive vision of the primary teaching staff evolution in León during the second half of the preceding century.